2013
DOI: 10.1038/bjc.2013.699
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated TGF-β receptors transduces a signal for epithelial–mesenchymal transition in colorectal cancer cells

Abstract: Background:Transforming growth factor-β (TGF-β) is a major inducer of epithelial–mesenchymal transition (EMT) in different cell types. TGF-β-mediated EMT is thought to contribute to tumour cell spread and metastasis. Sialyl Lewis antigens synthesised by fucosyltransferase (FUT) 3 and FUT6 are highly expressed in patients with metastatic colorectal cancer (CRC) and are utilised as tumour markers for cancer detection and evaluation of treatment efficacy. However, the role of FUT3 and FUT6 in augmenting the malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 47 publications
9
56
0
Order By: Relevance
“…Taken together, these findings suggest that loss of Smad4 may underlie the functional shift of TGF-␤ and BMP from a tumor suppressor to a tumor promoter. In addition, fucosylated TGF-␤ receptors are able to transduce a signal for EMT in CRC cells [74].…”
Section: Emt-related Signaling Pathwaysmentioning
confidence: 99%
“…Taken together, these findings suggest that loss of Smad4 may underlie the functional shift of TGF-␤ and BMP from a tumor suppressor to a tumor promoter. In addition, fucosylated TGF-␤ receptors are able to transduce a signal for EMT in CRC cells [74].…”
Section: Emt-related Signaling Pathwaysmentioning
confidence: 99%
“…For instance, the expression of the metastasis-suppressive gene Nm23-H1 in a human hepatocarcinoma cell line induces down-regulation of both FUTs and ST3GALs, resulting in reduced sLe x expression [62]. On the other hand, sLe antigens expressed on the TGF-β receptor enhance colon cancer cell migration through promotion of the epithelial to mesenchymal transition [63], which instead was found associated to the activity of the ST6GAL1 gene in other cancer cell lines [64]. …”
Section: Regulation Of Slea and Slexmentioning
confidence: 99%
“…These observations indicate a high requirement for L-fucose by various cancer cells [15]. Indeed, we, together with others, have reported that enhanced FUT activity facilitated the metastatic potential of colorectal cancer cells, thus highlighting this as a therapeutic target for cancer therapy [16]. …”
Section: Introductionmentioning
confidence: 51%
“…Such findings demonstrated that Notch-1 signaling maintained tumor growth, antiapoptotic signaling, epithelial-mesenchymal transition for cancer cell metastasis, angiogenesis, and cancer stem cell survival [5]. Our strategy to target cancer cells, which actively take up L-fucose to produce fucosylated proteins such as sialylated antigens and growth factors in response to Notch-1 activation, can be utilized for killing Notch-1-expressing cancer cells in the same manner [16]. As described in this report, our drug delivery system has the potential to specifically target cancer cells with reduced toxicity and high efficacy.…”
Section: Discussionmentioning
confidence: 99%